The weather conditions on rice yield in the State of São Paulo, Brazil - Silva, Gabriel L. S. Peixoto da; Vicente, José Roberto; Caser, Denise Viani (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this paper was to measure the effects of weather conditions on rice yield in the State of São Paulo, Brazil. Regression analysis was used to estimate the relation between crop yield and monthly hydric deficiencies. The results suggest great sensibility of rice to water deficiencies in January, February and March. Some of the adjusted models supply better yield forecasts than the field surveys, according to the adopted selection criteria.